PENERAPAN KONSELING KELOMPOK REALITAS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMK NEGERI 3 MAKASSAR - Nasratul Khumaerah (Program Studi bimbingan Konseling PPs UNM Makassar, 2015)
Pre-Experimental research was conducted in SMK Negeri 3 Makassar with a total of 10 people of class XI electricity as the subjects research. Problem in this study was students in class XI Electricity experiencing a low independence of learning.This study aims to: (1) Determine the description of the independence of student learning before the Implementation of Reality Group Counseling in SMK Negeri 3 Makassar (2) Be able to know illustration of students’ learning independence after Application of Reality Group Counseling in SMK Negeri 3 Makassar (3) Find out if there is a positive impact on Reality Group Counselling application to increase the independence of student learning in SMK Negeri 3 Makassar. Experimental subjects were given a pretest to determine the atmosphere of students’ learning independence before given reality counseling. At the end of the study, students were given a posttest to determine the effect of applying the reality group counseling in improving learning independence. Collecting data using questionnaires and observation. Analyzed using percentages and inferential statistical analysis, the t-test. The results showed that: (1) Independence learnt students at SMK Negeri 3 Makassar before the given technique Reality Group Counseling were in middle category, while the degree of independence for students at SMK Negeri 3 Makassar after given Reality Group Counseling technique has increased or at high category, (2) There were differences in the level of independent learning in SMK Negeri 3 Makassar before and after given the reality of group counseling techniques.